2019
DOI: 10.15407/spqeo22.03.267
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure, optical and photoelectrical properties of crystalline Si2Te3

Abstract: In the framework of the density functional theory (DFT) in the approximation of local density adjusted for the strong correlation (LDA+U method), calculated were the band structure, total and partial densities of electronic states, as well as the spatial distribution of the electron density. According to the results of the calculation, Si 2 Te 3 is an indirect-gap semiconductor with the calculated band gap calc gi E = 2.05 eV, close to the experimentally measured opt g E = 2.13 eV. The absorption edge and phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…n = 2 for direct band gap transitions and n = 1/2 for indirect band gap transitions. Previous work by Bletskan et al 22 indicated an indirect band gap value of 2.13 eV for crystalline Si 2 Te 3 at room temperature. Bhattarai et al 6 have also shown that the stress has a strong effect on the band gap energy as well as the nature of the transition (i.e., direct or indirect).…”
Section: Resultsmentioning
confidence: 91%
“…n = 2 for direct band gap transitions and n = 1/2 for indirect band gap transitions. Previous work by Bletskan et al 22 indicated an indirect band gap value of 2.13 eV for crystalline Si 2 Te 3 at room temperature. Bhattarai et al 6 have also shown that the stress has a strong effect on the band gap energy as well as the nature of the transition (i.e., direct or indirect).…”
Section: Resultsmentioning
confidence: 91%